THE CONTEMPORARY DANCE ACCORDING TO BALLET-DANCERS-CHOREOGRAPHERS (Fiep Bulletin - online, 2015)
This research of qualitative character, had as object of study to identify the sense of dance for contemporary ballet dancers-choreographers, through the survey of the singularities and regularities most present in the speech of this social group. Therefore, we carried through half-structuralized individual interviews with fourteen professionals among those who had been the most distinguished in the dance market of the city of Rio de Janeiro, between 1990 and 2000. This period comprises the historical moment when the so called contemporary dance jumps from the marginality's ghetto to the top of the professional market  phenomenon registered in the great urban centers of the occidental world. The methodological option adopted, based upon the studies of the Social Representations and of the Discourse Analysis, had as main references Orlandi (2000), Ansart (1978), Stoer (2004) and Backzo (1985). For this last one, through the speeches that a group attributes to itself, we can raise part of its imaginary. The results of the research pointed to the inadequacy of the use of the term contemporary dance for, according to the interviewed subjects, what exists is a multiplicity of tendencies that do not attach to one pre-defined form, methodology or style, but that varies as the vicissitudes of the creation. We found some regularities that compose a net of senses in which this different tendencies entangle, among which we distinguish the transit by the differences. Also occurs: the latent desire of transformation; the risk as attitude in life and in the dance; the valorization of the present moment as unique event and the search for an authorial discourse.
Keywords: social representations; contemporary dances; differences.